The nose--revision & reconstruction a manual and casebook - Behrbohm, Hans (Thieme Publishers, 2016)
This practical, how-to casebook provides expert guidelines and step-by-step instructions on managing the many complications that can come up in revision rhinoplasty and reconstructive surgery of the nose. The first part of the book discusses the principles and practice of revision rhinoplasty and the second part presents nearly 60 select cases that address common surgical problems and offer the best solutions for resolving them